Laminar burning velocity of n-butane/Hydrogen/Air mixtures at elevated temperatures. (1st June 2019) - Jithin, E.V.; Dinesh, Kadali; Mohammad, Akram; Velamati, Ratna Kishore
Abstract: The effect of hydrogen (H2 ) addition in the laminar burning velocity (LBV) of n-butane-air at elevated temperatures is described in this paper. For various equivalence ratios (ϕ), ranging from 0.7 to 1.3, LBV was measured for 20%, 40% and 60% H2 addition to n-butane using a preheated mesoscale diverging channel technique. Using this experimental technique, LBV measurements were conducted for unburnt mixture temperature up to 450 K. The maximum burning velocity has been obtained at equivalence ratio 1.1 for all the mixture conditions. The LBV results at atmospheric condition for n-butane-hydrogen-air mixture were obtained by extrapolating the experimental data at elevated temperatures. "Heat flux method" experimental setup was used for measuring the LBV of n-butane-hydrogen-air mixture at atmospheric condition. The results obtained for LBV at atmospheric conditions with the two different methods at 0%, 20%, 40% and 60% H2 composition in n-butane were found to be in good agreement. The experimental results of LBV for n-butane were compared with the numerical predictions using USC mech II, Aramco mech 2.0 and LLNL reaction mechanisms. The numerical predictions of LBV using Aramco mech 2.0 shows good agreement with experimental data at rich, lean and stoichiometric mixture conditions. Highlights: The effect of H2 addition in the LBV of n-butane is studied. LBV at elevated temperatures is measured using diverging channel setup. Temperature exponent decreases with addition of hydrogen.